Amyloid‐tau‐neurodegeneration (ATN) profiles and influence of age‐of‐onset on cognitive trajectories in a Southeast Asian cohort: SYNC project. (31st December 2021) - Vipin, Ashwati; Koh, Chen Ling; Wong, Benjamin; Zailan, Fatin Zahra; Tan, Yi Jayne; Soo, See Ann; Satish, Vaynii; Kumar, Dilip; Wang, Brian Zhiyang; Ng, Adeline Su Lyn; Chiew, Hui Jin; Ng, Kok Pin; et al.
Abstract: Background: The amyloid‐tau‐neurodegeneration (ATN) scheme enables unbiased biomarker‐based diagnoses, independent of cognitive status and temporal ordering of AD pathogenic mechanisms [Jack et al., 2016]. ATN profiles in the diverse Southeast‐Asian region will provide important insights into the ATN framework and its association with cognition [Hilal et al., 2017; Knopman et al., 2018]. We examined the effect of amyloid‐beta status on longitudinal cognitive trajectory in young and late‐onset patients as well as impact of ATN categories on longitudinal cognition in a Southeast‐Asian cohort. We hypothesized that age of onset would differentially influence the association between amyloid status and longitudinal cognition. Method: We studied 92 patients with cognitive impairment from the Singapore YouNg Dementia Cohort. Patients underwent structural‐MRI and lumbar puncture for cerebrospinal fluid amyloid‐beta (1–42), phosphorylated‐tau (p‐tau) and total‐tau (t‐tau) to assess biomarker positivity [Blennow et al., 2020]. A cut‐off age of 60 years was used to define young‐onset cognitive impairment. Separately, ATN profiles were assigned based on cerebrospinal fluid biomarker levels: normal biomarker profile (A‐T‐N‐), suspected non‐Alzheimer's pathology (SNAP: A‐T±N±) and Alzheimer's continuum (A+T±N±). Linear mixed effects models assessed longitudinal group differences in mini‐mental state examination (MMSE) trajectory. Result: Young (<60yrs) sporadic amyloid‐positive, patients demonstrated significantly greater decline in longitudinal MMSE scores (AmyloidStatus*AgeOfOnset*Time: β=2.82, p=0.0193; Fig. 1) compared to older (≥60yrs) amyloid‐positive counterparts. Across the three ATN categories, there were no differences in baseline age, sex, white matter hyperintensities, medial temporal atrophy or APOE4 status (Table 1). Patients along the Alzheimer's continuum showed a greater decline in MMSE scores over time compared to both normal biomarker A‐T‐N‐ (β=−2.23, p=0.001; Fig. 2‐3) and SNAP patients (β=−2.05, p=0.004; Fig. 2‐3). MMSE decline did not differ between SNAP and A‐T‐N‐ groups. Conclusion: We show steeper MMSE decline in young amyloid‐positive patients than their amyloid‐positive older counterparts. Additionally, Alzheimer's continuum patients showed steeper MMSE decline than A‐T‐N‐ and SNAP patients. These findings provide insights into mechanisms for the more aggressive cognitive decline frequently observed in younger patients.